Uma clínica para respirar - Lopérgolo, Ana Cristina Delgado (2009)
The present thesis has constituted itself from the survey of many practical possibilities in the dealings with a particular set of issues raised from the encounters of a psy as related to certain varieties of therapeutic initiatives. Under the inspiration of one of such initiatives the work carried out at the Peri-Peri Local Psychology Care Unit with babies and their parents this report´s chapters are structured using pregnancy as a metaphor. In the chapter named The Thesis Pre-history , there is a report about the author´s beginning professional path, before she started at the Ambulatório de Especialidades do Jardim Peri-Peri, when a certain design, a certain reference had constituted her as a therapist. In Part 1, or The First Trimester referring to the period when the author´s had already joined the Unit s children´s mental health care team the thesis maps the constitution of such clinical practice, from the viewpoint of both children psychiatry and psychoanalysis, and, still, it tries and approaches some issues as posed by this same practice at present. In Part 2, or The Second Trimester , the thesis explores the work carried out with the team in charge with the babies; maps some of the possible intervention strategies, charged with the effort of hearing the sufferings of such young patients the babies as well as the dealings with the sufferings of both parents and members of the rest of the team. Some therapeutic initiatives in which this psy took part are discussed. Such initiatives are based on a clinical practice which is politically prone to view the care unit in such a way so as to incite changes, resist to the processes which oppress subjectivities and to promote differences. After the third trimester, a baby is ready to be born. It is in The Third Trimester , that the Final Considerations are presented, stressing that the preparing of a psy is a never ending process, because of the impossibility of dissociation between practice and theory. The thesis is born !